2020
DOI: 10.1161/circresaha.119.315502
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1-Downregulation Aggravates Porphyromonas Gingivalis -Induced Atherosclerosis by Encouraging Oxidative Stress

Abstract: Rationale: Atherosclerotic cardiovascular diseases are the leading cause of mortality worldwide. Atherosclerotic cardiovascular diseases are considered as chronic inflammation processes. In addition to risk factors associated with the cardiovascular system itself, pathogenic bacteria such as the periodontitis-associated Porphyromonas gingivalis ( P gingivalis ) are also closely correlated with the development of atherosclerosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 58 publications
2
125
2
Order By: Relevance
“…Periodontal treatment has been shown to improve the endothelial function and reduce the biomarkers (such as CRP, IL-6, TNF-α, fibrinogen, triglycerides) of atherosclerotic disease, particularly in individuals already suffering from CVDs [ 29 ]. Trials in humans have found P. gingivalis in clinical samples at a detection rate of 82.61% by fluorescent in situ hybridization assay [ 30 ]. Subsequently, in vivo experiments confirmed the promoting effect of P. gingivalis on AS.…”
Section: Cardiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal treatment has been shown to improve the endothelial function and reduce the biomarkers (such as CRP, IL-6, TNF-α, fibrinogen, triglycerides) of atherosclerotic disease, particularly in individuals already suffering from CVDs [ 29 ]. Trials in humans have found P. gingivalis in clinical samples at a detection rate of 82.61% by fluorescent in situ hybridization assay [ 30 ]. Subsequently, in vivo experiments confirmed the promoting effect of P. gingivalis on AS.…”
Section: Cardiologymentioning
confidence: 99%
“…Subsequently, in vivo experiments confirmed the promoting effect of P. gingivalis on AS. Infection with P. gingivalis exacerbated atherogenesis in apolipoprotein E (ApoE)-deficient mice [ 2 , 30 ], and the proximal aortic lesion size in P. gingivalis -inoculated mice was 2-fold larger than that in control mice [ 2 ]. These results strongly suggest that P. gingivalis may enter the lesion area and promote the development of AS.…”
Section: Cardiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of immune inflammatory immunoreactive cells and pro-inflammatory cytokines have an obvious daily rhythm ( 80 ) and functionality of the immune system has been linked to the circadian clock ( 81 ). A recent study reported that circadian disruption by sleep fragmentation accelerates atherosclerosis development by increasing the number of circulating monocytes ( 82 ).…”
Section: Circadian Rhythm and Inflammatory Immunoreactionsmentioning
confidence: 99%
“…Rhythmic oscillations of gut microbiota were observed in diabetic mice as well as analysis of circulating metabolites showed changes in the daily concentration of metabolites of the histidine pathway and the metabolism of betaine, methionine, cysteine, followed by an increase in TMAO production ( Beli et al, 2019 ). Moreover, in the study of atherosclerosis, associated with infection of P orphyromonas gingivalis that causes periodontitis, circadian clock disruption enhanced atherosclerosis progression in Bmal1−/− ApoE−/− mice ( Xie et al, 2020 ). Despite of a number of studies on the influence of circadian rhythms on atherogenesis and the composition of gut microbiome and its metabolites, the mechanism of the influence of diurnal variations in the microbiome on the development of atherosclerosis is still an actual topic for research in the near future.…”
Section: The Role Of Microbiome Metabolites In the Development Of Athmentioning
confidence: 99%